Challenges of Fiscal Policy in Emerging and Developing Economies - Huidrom, Raju (World Bank, Washington, DC, 2016)
This paper presents a systematic analysis of the availability and use of fiscal space in emerging and developing economies. These economies built fiscal space in the run-up to the Great Recession of 2008-09, which was then used for stimulus. This reflects a more general trend over the past three decades, where availability of fiscal space has been associated with increasingly countercyclical (or less procyclical) fiscal policy. However, fiscal space has shrunk since the Great Recession and has not returned to pre-crisis levels. Emerging and developing economies face downside risks to growth and prospects of rising financing costs. In the event that these cause a sharp cyclical slowdown, policy makers may need to employ fiscal policy as a possible tool for stimulus. An important prerequisite for fiscal policy to be effective is that these economies have the necessary fiscal space to employ countercyclical policies. Over the medium-term, credible and well-designed institutional arrangements, such as fiscal rules, stabilization funds, and medium-term expenditure frameworks, can help build fiscal space and strengthen policy outcomes.